Preparation and Evaluation of Horse Chestnut Seed Extract Gel and its Effect on Varicose Disease Symptoms - H Asgari Rad; M Azadbakht; A Sharifpour; F Mazloom (Institue of Medicinal Plants, ACECR, 2007)
Background: A common varicose vein of the lower organs occurs for women four times more than men and nearly half of them are from a family suffering from varicose veins. This disease causes ambiguous ache, feeling pressure on feet after long time standing, feeling heaviness on feet, mild edema on ankle, skin ulceration near ankle. It seldom causes varicose veins to tear and bleed. Objective: The aim of this research is to survey how to provide herbaceous medicine containing the extract of Indian chestnut to treat varicose and its related primary clinical study. Methods: the extract of Indian chestnut was prepared and different formulations a suitable topical gel has been produced. After the standardization of the product, the drug and placebo effects on those suffering from varicose veins through random sampling has been evaluated. Results: The amount of the extract of Indian chestnut has determined 5.4%. In the performed clinical study the effect of the medicine in comparison with placebo about reducing ache, inflammation, feeling weight on feet values p < 0.000, edema valiums p < 0.05 and itching values p < 0.007 was meaningful and 86.4% of the consumers are generally satisfied with the product. Conclution: Drug from Aseculus hippocastanum extract can be useful in prevention and treatment of Varicose disease symptoms.